A flexible under-driven bionic climbing robot design. Issue 1 (1st March 2022) - Guo, Ai; Zeng, Chao; Li, Guo; Fang, Ranran; Liu, Yang; Li, Rui
Abstract: The study of a reliable bionic climbing robot to replace humans in dangerous work at height has been a hot and difficult research topic in the academic and engineering communities. Researchers have developed climbing robots such as magnetic adsorption, vacuum adsorption, claw-stick adhesion, bionic adhesion and wet adhesion, depending on the mode of adhesion. However, due to their single adhesion method and limited means of regulation, most of them can only climb under specific experimental conditions and cannot meet complex engineering environments such as variable diameter, roughness and curvature. In order to solve the above technical problems to a certain extent, this paper draws on the excellent grasping ability of primates and the excellent movement form of the inchworm to design a flexible under-driven bionic climbing robot, which includes under-driven fingers made of coupled rigid and soft materials, and a lightweight torsional and telescopic system with good climbing adaptability and variable diameter wall transition capability. The flexible under-driven fingers are made of coupled bones, joints, muscles and skin of different modulus. The telescopic system consists of an open round thin shell rod, a two-axis motor and a flexible torso. Based on the mechanical design, the flexible under-driven finger is fabricated and subjected to finite element simulations and experiments, which show that the flexible gripper has good gripping adaptability for different shapes of objects.